EXPLORING THE IMPACT OF LEADERSHIP STYLE, SCHOOL HEAD, SUPERVISION, BUDGET, AND INFRASTRUCTURE ON TEACHER COMPETENCE AND MOTIVATION AND ITS EFFECT ON STUDENT ACHIEVEMENT WITHIN UPTD EDUCATION IN PANCALANG KUNINGAN - Surya Permana, Indra; Sri Sedjati, Retina; Rasidin, Didin (Universitas Efarina, 2019)
This study aims to examine the influence of the leadership style of the UPTD head, the leadership style of the principal, the role of the school supervisor, BOS school and the infrastructure on student achievement by being mediated by the competence and motivation of the teacher. Data derived from the results of filling out questionnaires by as many as 124 respondents. Descriptive analysis was used to assess the average for each indicator of the research variable, followed by using the Partial Least Square technique with the help of the Smartpls program. The results of the study showed that the leadership style of the UPTD head, the leadership style of the principal and BOS funds did not affect the level of teacher competence, but it affected the motivation of the teacher. Likewise the role of school supervisors and infrastructure influences teacher competency, but does not affect teacher motivation, the high role of school supervisors and the complete facilities and infrastructure do not support teacher motivation but tend to influence teacher competency. While teacher motivation is not a determinant of high and low student achievement, but the high and low teacher competencies influence student achievement, this shows that the higher the teacher's competency, the higher student achievement.